Tobacco O-Methyltransferases Involved in Phenylpropanoid Metabolism. The Different Caffeoyl-Coenzyme A/5-Hydroxyferuloyl-Coenzyme A 3/5-O-Methyltransferase and Caffeic Acid/5-Hydroxyferulic Acid 3/5-O-Methyltransferase Classes Have Distinct Substrate Specificities and Expression Patterns - Maury, Stéphane (American Society of Plant Physiologists, 1999)
The biosynthesis of lignin monomers involves two methylation steps catalyzed by orthodiphenol-O-methyltransferases: caffeic acid/5-hydroxyferulic acid 3/5-O-methyltransferases (COMTs) and caffeoyl-coenzyme A (CoA)/5-hydroxyferuloyl-CoA 3/5-O-methyltransferases (CCoAOMTs). Two COMT classes (I and II) were already known to occur in tobacco (Nicotiana tabacum) and three distinct CCoAOMT classes have now been characterized. These three CCoAOMT classes displayed a maximum level of expression at different stages of stem development, in accordance with their involvement in the synthesis of lignin guaiacyl units. Expression profiles upon tobacco mosaic virus infection of tobacco leaves revealed a biphasic pattern of induction for COMT I, COMT II, and CCoAOMTs. The different isoforms were expressed in Escherichia coli and our results showed that CCoAOMTs and, more surprisingly, COMTs efficiently methylated hydroxycinnamoyl-CoA esters. COMT I was also active toward 5-hydroxyconiferyl alcohol, indicating that COMT I that catalyzes syringyl unit synthesis in planta may operate at the free acid, CoA ester, or alcohol levels. COMT II that is highly inducible by infection also accepted caffeoyl-CoA as a substrate, thus suggesting a role in ferulate derivative deposition in the walls of infected cells. Tobacco appears to possess an array of O-methyltransferase isoforms with variable efficiency toward the diverse plant o-diphenolic substrates.